The evolution and history of human populations in South Asia: inter-disciplinary studies in archaeology, biological anthropology, linguistics and genetics - Petraglia, M (Springer, 2007)
South Asia is home to a diverse range of prehistoric and contemporary cultures that include foragers, pastoralists, and farmers. In this book, archaeologists, biological anthropologists, geneticists and linguists are brought together in order to provide a comprehensive account of the history and evolution of human populations residing in the subcontinent. A wide range of topics and issues are addressed in this book, including hominin adaptations, behaviours, and dispersals; the origin and spread of food producing economies; and the cultural, biological and genetic relationship of foragers and settled communities. New theories, methodologies and interpretations presented in this book are bound to have a profound effect on the way in which the cultural record of South Asia is perceived and how this evolutionary history relates to events in the wider world.